2015
DOI: 10.1001/jamadermatol.2015.1986
|View full text |Cite
|
Sign up to set email alerts
|

Association of Psoriatic Disease With Uveitis

Abstract: IMPORTANCE Psoriasis, psoriatic arthritis, and uveitis are inflammatory disorders with significant overlap in their inflammatory pathways. Limited evidence is available about the relationship between psoriatic disease and uveitis.OBJECTIVE To investigate the potential bidirectional relationship between psoriatic disease, including psoriasis and psoriatic arthritis, and uveitis. DESIGN, SETTING, AND PARTICIPANTSWe performed a nationwide cohort study of the Danish population from January 1, 1997, through Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 36 publications
5
40
1
5
Order By: Relevance
“…Recent Danish and Taiwanese nationwide cohort studies, using administrative data, have reported an increased risk of uveitis associated with psoriatic disease 5 6. The Danish study demonstrated a bidirectional association, with patients with psoriasis and PsA having an increased risk of uveitis and patients with uveitis having an increased risk of psoriasis and PsA, suggesting a shared pathogenic pathway 5. Another study, using the same Danish data source, has reported an increased risk of Crohn’s disease and ulcerative colitis among patients with psoriasis and PsA,7 as have two studies using data from US Health Claims databases,8 9 and one looking at PsA using data from an Israeli healthcare database 10.…”
Section: Introductionmentioning
confidence: 95%
“…Recent Danish and Taiwanese nationwide cohort studies, using administrative data, have reported an increased risk of uveitis associated with psoriatic disease 5 6. The Danish study demonstrated a bidirectional association, with patients with psoriasis and PsA having an increased risk of uveitis and patients with uveitis having an increased risk of psoriasis and PsA, suggesting a shared pathogenic pathway 5. Another study, using the same Danish data source, has reported an increased risk of Crohn’s disease and ulcerative colitis among patients with psoriasis and PsA,7 as have two studies using data from US Health Claims databases,8 9 and one looking at PsA using data from an Israeli healthcare database 10.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, the case of patients with arthritis and familiar psoriasis provides a PsA subset classified as sine psoriasis (8). In addition, in recent years the increase of clinical studies have outlined how PsA can be associated with extrarticular manifestations, also alternatively recognized as comorbities (9)(10)(11)(12)(13). Among these, the most frequent are represented by uveitis (9), colitis (10), metabolic syndrome (MS) (11) and involvement of the cardiovascular system (12).…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%
“…In addition, in recent years the increase of clinical studies have outlined how PsA can be associated with extrarticular manifestations, also alternatively recognized as comorbities (9)(10)(11)(12)(13). Among these, the most frequent are represented by uveitis (9), colitis (10), metabolic syndrome (MS) (11) and involvement of the cardiovascular system (12). Psychological aspects, such as depressive symptoms and anxiety, represent important correlates of health related quality of life (HRQoL) (13).…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%
“…Autoimmune diseases that are more often associated with uveitis include rheumatoid arthritis and Behçet's disease, but other conditions are also prone to uveitis development, with significant overlap in their inflammatory pathways, including psoriasis and psoriatic arthritis (PsA) (Egeberg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…FIG URE 1 Severe plaque type psoriasis (PASI 22), before starting ustekinumab treatment FIG URE 2 Complete psoriasis remission at Week 163 | DI SCUS SIONPopulation studies have recently confirmed a bidirectional association between uveitis and various forms of psoriasis and psoriatic arthritis, suggesting a prompt ophthalmologist examination to detect ocular comorbidity as well as appropriate skin and joint evaluation in patients with uveitis(Egeberg et al, 2015; Yang et al, 2016). She had been treated by a rheumatologist and given 3.0 mg/kg per day cyclosporine A, with some improvement of the ocular manifestations, until a sudden worsening of both psoriasis (Psoriasis Area Severity Index, PASI: 12.7) and uveitis (UV) occurred in March 2015, with severe visual impairment.…”
mentioning
confidence: 99%